(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
The environmental conditions of our planet are rapidly degrading, mainly because of the large amounts of waste generated around the world. Brazil is the 4th largest waste generator besides it has a low recycling rate (1.28%), what reveals that the approach to environmental education in schools becomes increasingly urgent. It is essential to work with this theme since childhood through approaches that are capable to attract young people and to generate engagement and participation. In this context, the use of active methodologies combined with approaches that promote creativity appears as an alternative with potential benefits. The present work is an experience report about an extension project carried out with students from the 3rd to 5th year of elementary school in a public school in the city of XXXXX / RS, which aimed to work on environmental education through activities that encourage creativity. There were held eight in which a debate was held on topics related to the 3 R’s (Reduce, Reuse and Recycle), followed by a dynamic activity and a final conversation on the topic worked on. It was noticed a great engagement of students in the activities carried out and that they built positive reflections about the themes worked on. Along with environmental education, creativity was encouraged and developed, which is a positive fact, as it is known that creativity is important in adult life, both personally and professionally. Finally, it can be affirmed that the objectives have been achieved and that extension projects such as this one, which work in different ways under an interdisciplinary approach, can be successfully applied in several themes related to environmental education.